High volume fabrication of laser targets using MEMS techniques. (April 2016) - Spindloe, C; Arthur, G; Hall, F; Tomlinson, S; Potter, R; Kar, S; Green, J; Higginbotham, A; Booth, N.; Tolley, M K
Abstract: The latest techniques for the fabrication of high power laser targets, using processes developed for the manufacture of Micro-Electro-Mechanical System (MEMS) devices are discussed. These laser targets are designed to meet the needs of the increased shot numbers that are available in the latest design of laser facilities. Traditionally laser targets have been fabricated using conventional machining or coarse etching processes and have been produced in quantities of 10s to low 100s. Such targets can be used for high complexity experiments such as Inertial Fusion Energy (IFE) studies and can have many complex components that need assembling and characterisation with high precision. Using the techniques that are common to MEMS devices and integrating these with an existing target fabrication capability we are able to manufacture and deliver targets to these systems. It also enables us to manufacture novel targets that have not been possible using other techniques. In addition, developments in the positioning systems that are required to deliver these targets to the laser focus are also required and a system to deliver the target to a focus of an F2 beam at 0.1Hz is discussed.